Maternal Cardiac Function after Normal Delivery, Preeclampsia, and Eclampsia: A Prospective Study - Elena Timokhina; Tatiana Kuzmina; Alexander Strizhakov; Elena Pitskhelauri; Irina Ignatko; Vera Belousova (Hindawi Limited, 2019)
Introduction. The aim of this study is to assess maternal cardiac function in the postpartum period, after 2 and 6 months in the parturient with preeclampsia and eclampsia. Materials and Methods. Prospective study: 90 postpartum women after preeclampsia and eclampsia and 55 patients after an uncomplicated pregnancy. The parameters of maternal hemodynamics were recorded on days 1, 3, 5, 9, and 14 of postpartum period, after 2 and 6 months. The cardiac parameters were assessed. Results. PE is accompanied by increased peripheral vascular resistance. The indicator of vascular resistance, SVR, is elevated for both mild and severe PE. With mild PE, a significant increase in SVR is observed up to 5 days of postpartum period, with severe PE/E up to 9 days. We found that in case of severe PE, SVR remains elevated to 6 months after delivery. The parameters of the contractile function of the heart (ESV, EDV, SV, SI, CO, СI, MVCF) were significantly decreased: with mild PE up to 5-9 days, with severe up to 9-14 days of puerperia. ESV, SV, SI, CO, and CI remain low with severe PE up to 6 months. The revealed decreasing of contractile function of the heart is a sign of asymptomatic heart failure. Conclusions. The hemodynamics of the puerperas after PE and E is characterized by impaired contractility of the myocardium and an increase in the indices of peripheral resistance. The degree of deviation in the parameters of cardiac hemodynamics and vascular resistance depended on the severity of hypertensive complications of pregnancy.